Comparison of depression levels of elite wrestling and taekwondo athletes - Emrah Yılmaz; Mahmut Alp; Mehmet Kumartaslı; Sinan Gokbel (Selcuk University, 2015)
The aim of this study is to compare depression levels of elite wrestling and taekwondo athletes. To the study, 130 elite wrestlers and 130 elite taekwondo athletes who are now competiting in the league between Universities. "Beck Depression Inventory" was used to define the depression levels of the athletes. For analyzing datas, SPSS 18 (Statistical Package for the Social Sciences) was used. For analyzing datas statistically, Independent Sample t Test was done. As a result of test depression levels of elite wrestling and taekwondo athletes , the difference between groups was found to be statistically significant (p lt;0,05). To conclude our study, elite wrestler were defined more depressive than elite taekwondo athletes, so both of branches needed psychiatric examination according to possibility situation of the inventory.